Swift 4 recipes : hundreds of useful hand-picked code snippets - Zafirópulos, Yanis (Apress, 2019)
Get the most out of Swift 4 with this carefully compiled collection of select code snippets designed to solve everyday coding problems. This book features the Apress easy-to-use recipe format, with step-by-step instructions, and a no-fuss approach. You'll explore a wide range of topics, all neatly organized according to the language's own core elements and building blocks. You'll review common topics such as conditionals, loops, functions, classes, closures, and arrays. This book also includes recipes to some more advanced problems found in files, system programming, and algorithms. With Swift 4 Recipes, your programming problems are easily resolved, without wading through paragraphs of text.